Listeria innocua isolated from diseased ruminants harbour minor virulence genes of L. monocytogenes. Issue 2 (18th January 2022) - Matto, Carolina; D'Alessandro, Bruno; Mota, María Inés; Braga, Valeria; Buschiazzo, Alejandro; Gianneechini, Edgardo; Varela, Gustavo; Rivero, Rodolfo
Abstract: Listeriosis is one of the most common nervous diseases in ruminants, and is caused almost exclusively by the Gram‐positive bacterium, Listeria monocytogenes . However, there are few reports of listeriosis associated with L. innocua, which is genetically closely related to L. monocytogenes, but considered non‐pathogenic. In this work, we report two cases of suppurative meningoencephalitis in apparently previously healthy ruminants from different farms, in which two strains of L. innocua were recovered. The whole genomes from both isolates were sequenced, allowing phylogenetic analyses to be performed, which indicated that the two strains were very closely related. Virulence determinants were searched, especially genes coding for the main L. monocytogenes virulence factors which have been previously described in L. innocua . Surprisingly, the two isolates do not possess such virulence determinants. Instead, both strains carried a set of genes that encode for other virulence factors of the genus Listeria detected  using the Virulence Factor Database (VFDB): iap (division and invasion of host cells), lpeA (entry into non‐professional phagocytes cells), fbpA (multifunctional virulence factor, including adherence to host cells), lspA (surface protein anchoring), lap (adhesion to enterocytes and trans epithelial translocation), pdgA (resistance to lysozyme), oatA (resistance to different antimicrobial compounds and also required for growth inside macrophages), lplA1 (use of host‐metabolites for in vivo growth), gtcA (catalyses teichoic acid of bacterial wall), prsA2 (cell invasion, vacuole lysis and intracellular growth), clpC, clpE and clpP (survival under several stress conditions). These genes among others detected, could be involved in the ability of L. innocua to produce damage in animal and human hosts. These results highlight the multifactorial profile of Listeria pathogenesis and the need for comprehensive scientific research that address microbiological, environmental and veterinary aspects of listeriosis. Abstract : This paper report two cases of nervous listeriosis in ruminants due to L. innocua in which their genomes were sequenced, and the presence of virulence factors were studied.